Makes caterpillars floppy toxins Mcf1 and Mcf2 from Photorhabdus luminescens - Heilen, Philipp (Technische Universität Dortmund, 2025)
The Makes caterpillars floppy toxins Mcf1 and Mcf2 are essential virulence factors from Photorhabdus luminescens, that ensure the survival of the bacterium and its symbiotic nematodes. In my thesis I solved the structure of Mcf1 (3.6 Å) and described Mcf2 as more instable and flexible, which prevented high resolution structure determination but still gave rise to a partial cryo-EM density. Both toxins consist of an N-terminal effector domain (NED), activator binding domain (ABD), protease effector domain (PED), two putative translocation domains (TD) and three putative receptor-binding domains (RBD). While the general structure resembles the ABCD toxin family, the translocation domains in particular are similar to the translocase of large clostridial toxins (LCT). Finally, I identified Arf3 as the cytosolic activator of both toxins and could formulate an activation mechanism that causes the release of the NED and PED into the cytosol, where both act independently as toxic effectors that contribute to the high potency of the Mcf toxins.
Keywords: Photorhabdus luminescens; Makes caterpillars floppy toxins; Cryo-EM; Mcf1; Mcf2; 570; 540